IMPLEMENTATION OF CASH ACCOUNTING SYSTEM AT BPR SHARIA TAMAN INDAH DARUSSALAM - Suprihatin Ningsih; Riska Amelia Nabila (Az-Zahra Media Society, 2025)
This study aims to determine the implementation of the cash receipts and disbursements accounting system at BPR Sharia Taman Indah Darussalam, ensure its compliance with sharia principles and applicable regulations, and evaluate the quality of internal controls. This study employed a descriptive qualitative approach, collecting data using observation, interviews, and documentation. The results indicate that the cash receipts and disbursements accounting system at BPR Sharia Taman Indah Darussalam is generally in accordance with Sharia principles, and its implementation complies with the regulations in Sharia Financial Accounting Standards (PSAK). Internal controls at the institution are considered adequate even though several challenges remain, such as limited human resources (HR) and technology. These findings indicate that BPR Syariah Taman Indah requires efforts to improve its human resources (HR) and technology to ensure the smooth implementation of the cash accounting system in accordance with applicable regulations.